Daud's Fasting Habituation And The Development Of Delayed Gratification: A Phenomenological Study Of Boarding School Student - Naufal Zuhdi 'Afif; Luthfiah Tri Yunita; Muchammad Aji; Alwi Hakim (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study aims to examine students' experiences in practicing the fast of Daud and its implications for delayed gratification skills from an educational psychology perspective. The study employed a qualitative, descriptive phenomenological approach at the Al-Mumtazah Muhammadiyah Modern Islamic Boarding School in Ajibarang, with purposively selected subjects. Data were collected through in-depth interviews, observation, and documentation, then analyzed using Moustakas' phenomenological model. The results indicate that the fast of Daud is interpreted as a means of self-control, discipline, and spiritual closeness. This practice fosters the ability to delay gratification, control emotions, and increase responsibility for learning. The findings also indicate that the success of the practice is influenced by internal motivation and support from the Islamic boarding school environment. This study confirms that the fast of Daud contributes to the development of student self-regulation and is relevant as an experiential character learning model in Islamic education.